Implementation of 48V/350W BLDC Motor Speed Control With PID Method Using Microcontroller-Based Sensorless Techniques - Maula, Nurizka Fitra; Ilman, Sofyan Muhammad; Yahya, Sofian (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
A brushless direct current (BLDC) motor is widely used in automotive and industrial applications due to its low noise and high performance. However, traditional BLDC motor control relies on Hall-effect sensors, which increase costs, enlarge motor dimensions, and risk errors from sensor failures. This research focuses on implementing a sensorless control system for a 350W, 48V BLDC motor. The goal is to achieve stable operation at a set speed of 250 rpm, with a steady-state error â‰¤3%, under varying loads from 0 Nm to 2.7 Nm. Using the Ziegler-Nichols PID tuning method, the study was conducted in the Electrical Machinery Laboratory at Bandung State Polytechnic. The results show that the sensorless control system effectively maintains setpoint speeds of 90 rpm, 120 rpm, 200 rpm, and 250 rpm. At 250 rpm, the system achieved an average steady-state error of 2.44% using PID parameters Kp = 3.13, Ki = 8.69, and Kd = 0.25. The motor's output power ranged from 136.88W at minimum load to 297.92W at maximum load, demonstrating improved efficiency and system performance